Threats of leaf spots of Sigatoka (Mycosphaerella spp.) in sustainable ecuadorian banana production - Palacios, Christian Mauricio; Regalado, Jorge Osiris Garcia; Plaza, Jacinto Augusto Marcillo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
This study reveals the vulnerability of the Ecuadorian banana industry to diseases caused by leaf spotting of Sigatoka, which affects the productivity of banana plantations. The pathogen was described and information was collected from several scientific articles and studies in banana producer’s countries, as a result of the theoretical review evidence of reduced production, increased doses and applications of fungicides. Generating a greater environmental impact as a result of the phytosanitary control mechanisms that in turn increase production costs becoming an unsustainable production system.